Vegetative mobility in ontomorphogenesis of Potentilla reptans L. (Rosaceae) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
The data on the shoot formation, types of buds, different age groups of plants and the peculiarities of the specialized and non-specialized vegetative reproduction are given in the article. Five stages of morphogenesis are shown. The features of spatial structure of individuals are described.
Keywords: age group, particulation, bud, shoot formation.